Facilitating an evolving service user involvement group for people with dementia: what can we learn?. Issue 2 (9th May 2016) - Kenny, Jocelyne; Asquith, Ian; Guss, Reinhard; Field, Elizabeth; Slade, Lewis; Bone, Alexandra; Oliver, Keith; Jones, Mark; Ryan, Chris; Brooks, Melvyn; Norris, Chris
Abstract : Purpose: – The purpose of this paper is to demonstrate how service user involvement for people living with a diagnosis of dementia can contribute to innovate ways of training and educating a skilled healthcare workforce. Design/methodology/approach: – The paper uses a case study approach, including interviews observations and reflections from facilitators and members of a service user group for people living with dementia in a recovery-based older adult service in East Kent, UK. In total, 11 people were involved in this study: five people are living with a diagnosis of dementia, two are clinical psychologists, two are trainee clinical psychologists and two are placement year psychology undergraduates. Findings: – The paper shows how service user involvement groups can enable people with dementia to train a wide range of healthcare professionals in different areas, from the perspective of people living with dementia and healthcare professionals. It also reflects on the challenges that can arise through working with patients in a more collegiate way. Originality/value: – This paper demonstrates that people with dementia can be involved in the training of healthcare professionals in innovative ways. It therefore suggests new ways of working with people with dementia to develop staff skills.